Transport mechanisms between the endocytic, recycling, and biosynthetic pathways via endosomes and the trans-Golgi network - Toshima, Junko Y.; Toshima, Jiro (Frontiers in Cell and Developmental Biology, 2024)
After the endocytic and biosynthetic pathway converge, they partially share the route to the lysosome/vacuole. Similarly, the endocytic recycling and secretory pathways also partially share the route to the plasma membrane. The interaction of these transport pathways is mediated by endosomes and the trans-Golgi network, which act as sorting stations in endocytic and biosynthesis pathway, and endosomes has a bidirectional transport pathway to and from the TGN. In mammalian cells endosomes can be largely classified as early/sorting, late, and recycling endosomes, based on their morphological features and localization of Rab family proteins, which are key factors in vesicular trafficking. However, these endosomes do not necessarily represent specific compartments that are comparable among different species. For instance, Rab5 localizes to early endosomes in mammalian cells but is widely localized to early-to-late endosomes in yeast, and to the pre-vacuolar endosome and TGN in plant cells. The SNARE complexes are also key factors widely conserved among species and localized specifically to the endosomal membrane, but the localization of the respective homologs is not necessarily consistent among species. These facts suggest that endosomes should be classified more inclusively across species. Here we reconsider the mammalian endosome system based on findings in budding yeast and other species and discuss the differences and similarities between them.